Skin Cancers and Lung Transplant - Wilken, Reason; Carucci, John; Stevenson, Mary L. (Seminars in Respiratory and Critical Care Medicine, 2021)
It is well known that solid-organ transplant recipients (SOTRs) have a 65- to 100-fold increase in the risk of developing skin cancer, namely, nonmelanoma skin cancers (NMSCs) such as cutaneous squamous cell carcinoma (cSCC) and basal cell carcinoma (BCC). In addition, these patients are also at increased risk for development of melanoma as well as other less common cutaneous malignancies (Merkel's cell carcinoma, Kaposi's sarcoma). SOTRs with NMSC (namely cSCC) are also at significantly increased risk of poor clinical outcomes including local recurrence, nodal and distant metastasis, and disease-specific death relative to patients who are not immunosuppressed. Increased surveillance and monitoring in patients at risk of aggressive disease and poor outcomes who are on immunosuppression is essential in patients with lung transplants given the high degree of immunosuppression. Increased awareness of risks, treatments, and management allows for improved outcomes in these patients. This article will provide an overview of the risk factors for the development of cutaneous malignancies in organ transplant recipients as well as a detailed discussion of various immunosuppressant and prophylactic medications used in this patient population that contribute to the risk of developing cutaneous malignancies, with an emphasis on NMSC (cSCC and BCC) in lung transplant recipients. Finally, this article includes a discussion on the clinical and dermatologic management of this high-risk immunosuppressed population including a review of topical and systemic agents for field therapy of actinic damage and chemoprevention of keratinocyte carcinomas. In addition, indications for additional treatment and preventive measures such as adjuvant radiation treatment after surgical management of cutaneous malignancies and potential modification of immunosuppressive medication regimens are discussed.
Keywords: skin cancer; immunosuppression; lung transplant; squamous cell carcinoma; melanoma; merkel cell carcinoma